A Credibility Assessment Approach for Scenario-Based Virtual Testing of Automated Driving Functions - Stadler, Christoph; Montanari, Francesco; Baron, Wojciech; Sippl, Christoph; Djanatliev, Anatoli (IEEE Open Journal of Intelligent Transportation Systems, 2022)
An immense test space is pushing the development and testing of automated driving functions from real to virtual environments. The virtual world is provided by interconnected simulation models representing sensors, vehicle dynamics, and both static and dynamic environment. For the virtual validation of automated driving, special attention must be paid to the simulation’s credibility, which can be impaired by inappropriate or inaccurate simulation models and tools. Therefore, in this work a method is proposed to assess the credibility of simulation-based testing for automated driving. The approach allows a qualitative and relatively quantitative comparisons between scenarios as well as between different simulation setups. Therefore, several uni- and multivariate metrics are applied towards a scoring of similarity of the behavior between simulation and real test drive. This is achieved by using ground truth data in form of simulation scenarios from real world measurement data. In this way, the virtual automated vehicle encounters the same conditions and surroundings than its counterpart in the real world for evaluating their similarity. The practical applicability of the proposed credibility assessment approach is demonstrated in a case study, in which the credibility of an exemplary simulation-based test bench is inferred.
Keywords: automated driving; software-in-the-loop; scenario-based approach; virtual testing; virtual development; virtual validation; computer simulation; automotive engineering; intelligent vehicles; automated vehicles

ITANS: Incremental Task and Network Scheduling for Time-Sensitive Networks - Arestova, Anna; Baron, Wojciech; Hielscher, Kai-Steffen; German, Reinhard (IEEE Open Journal of Intelligent Transportation Systems, 2022)
Recent trends such as automated driving in the automotive field and digitization in factory automation confront designers of real-time systems with new challenges. These challenges have arisen due to the increasing amount of data and an intensified interconnection of functions. For distributed safety-critical systems, this progression has the impact that the complexity of scheduling tasks with precedence constraints organized in so-called cause-effect chains increases the more data has to be exchanged between tasks and the more functions are involved. Especially when data has to be transmitted over an Ethernet-based communication network, the coordination between the tasks running on different end-devices and the network flows has to be ensured to meet strict end-to-end deadlines. In this work, we present an incremental heuristic approach that computes schedules for distributed and data-dependent cause-effect chains consisting of multi-rate tasks and network flows in time-sensitive networks. On the one hand, we provide a common task model for tasks and network flows. On the other hand, we introduce the concept of earliest and latest start times to speed up the solution discovery process and to discard infeasible solutions at an early stage. Our algorithm is able to solve large problems for synthetic network topologies with randomized data dependencies in a few seconds on average under strict end-to-end deadlines. We have achieved a high success rate for multi-rate cause-effect chains and an even better result for homogeneous or harmonic chains. Our approach also showed low jitter for homogeonous cause-effect chains.
CRIS-Team WoS Importer:2022-05-27

LETT: An Execution Model for Distributed Real-Time Systems - Baron, Wojciech; Arestova, Anna; Sippl, Christoph; Hielscher, Kai-Steffen; German, Reinhard (2021 IEEE 94th Vehicular Technology Conference (VTC2021-Fall), 2021)
The architecture of modern vehicles is shifting from multiple rather loosely collaborating single-core systems to fewer tightly collaborating high-performance multi-core systems. This architectural shift is intended to be capable of managing the increased computational and communication effort that is required to run advanced driver assistance and automated driving software. The most widespread real-time execution model is based on bounded worst-case execution times of tasks, which can result in weaknesses with regard to data determinism in multi-core systems. Therefore, an alternative execution model in which the execution time is abstracted by a logical time has emerged. This execution model proved its feasibility in practical use cases on multi-core systems under the assumption, that data transmission can be performed in zero time. However, this assumption is difficult to meet, especially for distributed realtime systems. In this paper, we propose an execution model in which a logical transmission time is introduced in addition to the logical execution time. The proposed execution model not only allows the prerequisite of zero read and write times to be discarded, but also the scheduling of read and write processes at a fixed point in time is no longer necessary. Consequently, we validate the proposed execution model in a case study and discuss advantages and disadvantage
Keywords: Distributed Real-Time Systems; Automated Driving Architecture; Logical Execution Time

Performance Evaluation of HLA RTI Implementations - Gütlein, Moritz; Baron, Wojciech; Renner, Christopher; Djanatliev, Anatoli (Proceedings of the 2020 IEEE/ACM 24st International Symposium on Distributed Simulation and Real Time Applications (DS-RT) 2020, 2020)
The High Level Architecture is an IEEE standard that enables distributed simulation. There are several implementations of the standard, which are providing i.a. the Run-Time Infrastructure component. This paper compares the four most known RTI Implementations, namely MAK RTI, Pitch pRTI, Portico, and CERTI, with a focus on performance evaluation. In general, Pitch pRTI was the fastest implementation for most of our experiments. CERTI performed best for big payload sizes and Portico showed an interesting oscillation pattern.<br
Keywords: High Level Architecture; HLA; Distributed Simulation; Performance; Middleware; RTI

Repeatable Simulation for Highly Automated Driving Development and Testing - Baron, Wojciech; Sippl, Christoph; Hielscher, Kai-Steffen; German, Reinhard (Proceedings of the 2020 IEEE 91st Vehicular Technology Conference (VTC2020-Spring), 2020)
The development and testing of automated driving functions in the real world is costly and time-consuming. For this reason, software for automated driving is at first developed and tested in a virtual environment. The provision of the virtual environment requires the coupling of several simulation tools and models. The result is a co-simulation with a feedback loop from the automated driving function to the virtual environment, that does not necessarily exhibit deterministic behavior. However, determinism is a desirable property for developers to be able to analyze the automated driving function and for testers to be able to implement test automation. This paper identifies sources of non-determinism in co-simulation setups for automated driving and proposes a master-less coupling approach that allows repeatable executions. The results are demonstrated using an exemplary driving scenario and compared to a traditional coupling method that uses physical clock synchronization. The presented approach adds some overhead to the simulation modeling and execution, but ensures repeatable simulation results in any cas
Keywords: Automated Driving; Software-in-the-Loop; Co-Simulation; Distributed Simulation; Virtual Environment

Synchronization of Hybrid Models in the Automated Driving Simulation - Baron, Wojciech; Sippl, Christoph; Hielscher, Kai-Steffen; German, Reinhard (IEEE Vehicular Technology Conference, 2022)
Developing and testing automated driving functions on public roads or proving grounds is time-consuming and expensive. Driving in virtual environments is increasingly seen as an eligible approach to counteract these drawbacks. The virtual environment is provided by one or more simulation tools and is coupled with software modules of the automated driving function. This results in a feedback loop that controls a virtual vehicle. Since simulation runs are carried out on off-the-shelf computers, determinism issues may occur due to race conditions. However, determinism is a desirable property in order to be able to reasonably benchmark the automated driving function. This work identifies execution patterns of software modules and shows how they can be synchronized by means of mapping to discrete event semantics. The resulting simulation setup produces repeatable results independent of the available computing and network power. The results are demonstrated using an exemplary driving scenario and compared to paced real-time simulation.
CRIS-Team Scopus Importer:2022-09-30
Keywords: Automated Driving Simulation; Hybrid Discrete Event; Software-in-the-loop